The Psycholinguistic Markers of Individual Speech in Different Emotional States - Odintsova, Anastasia М. (Psychological Prospects Journal, 2017)
The article presents the results of the experimental and diagnostic research of persons’ psycholinguistic markers that provide an opportunity to distinguish various emotional and psychic states. The author revealed the meaning of the concept «emotional state» and distinguished the features of the external expression of persons’ emotional states in the process of realization their vital roles and perception of the other people’s roles. The research of psycholinguistic markers was carried out using the analyzing of author’s tales. The author demonstrated the effectiveness of the application of the fairytale therapy`s methods, in particular, fairytale analysis, for the identify of persons’ psycholinguistic markers of the various emotional and psychic states at the theoretical and empirical levels. The article describes the results of empirical research, which was carried out in three stages. The first stage was a diagnostic research, in which the author’s application form “Attitude to one’s own role” and the R. Cattell’s method of the personality’s multifactorialresearch (Form C) were used. The procedure of the factor analysis was performed at the second research stage. The goal of the third stage was the qualitative analysis of the fairytale material. The students aged 18 to 23 years participated in this study. The psycholinguistic markers corresponding to each type of the vital role and typical emotional states were identified. The scientific novelty of this research is that the emotional states were recognized by using of fairytale analysis at empirical level for the first time. The results can be used for creating and constructing of diagnostic and therapeutic methods in further psycholinguistic researches.Keywords: emotional states, vital role, fairytale analysis, psycholinguistic marker, life path.